PENGEMBANGAN MODEL PEMBELAJARAN TEMATIK BERDASARKAN BRAIN BASED LEARNING BERORIENTASI MULTIPLE INTELLIGENCES - Rulyansah, Afib (PEDAGOGY, 2017)
Problems that occur teachers are less able to develop thematic learning in primary schools. Develop thematic learning models one of the right steps to strengthen students basic skills. This research was conducted in Class IV SDN Kebonsari 5 Kota Probolinggo with the aim to produce thematic learning model based on Brain Based Learning Oriented Multiple Intelligences. The resulting product is a thematic learning model based on Brain Based Learning Oriented Multiple Intelligences which has a level of validity and stability. Development method with Bord and Gall model. The results of this study showed that the validation test results of experts stated very valid with the average score of 87.8%. Level of product absorption with score 84%. Key Words: thematic learning, brain based learning.